2009
DOI: 10.1007/s00259-009-1205-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of unknown primary neuroendocrine tumours (CUP-NET) using 68Ga-DOTA-NOC receptor PET/CT

Abstract: Our data indicate that (68)Ga-DOTA-NOC PET/CT is highly superior to (111)In-OctreoScan (39% detection rate for CUP according to the literature) and can play a major role in the management of patients with CUP-NET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
154
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(175 citation statements)
references
References 38 publications
11
154
0
10
Order By: Relevance
“…There are few reports of case series in the literature on patients with unknown primary tumors imaged with 68 Ga-DOTA-octreotide analogs (DOTATOC, DOTANOC, or DOTATATE). The largest study was reported by Prasad et al with 68 Ga-DOTANOC in 59 patients with metastatic NETs (17). In this latter study, the reported detectability of primary tumor with 68 Ga-DOTANOC was higher at 59%, although 49% of the positive scans for primary tumor were unconfirmed and surgical histopathology was available in 17% of patients.…”
Section: Discussionmentioning
confidence: 71%
“…There are few reports of case series in the literature on patients with unknown primary tumors imaged with 68 Ga-DOTA-octreotide analogs (DOTATOC, DOTANOC, or DOTATATE). The largest study was reported by Prasad et al with 68 Ga-DOTANOC in 59 patients with metastatic NETs (17). In this latter study, the reported detectability of primary tumor with 68 Ga-DOTANOC was higher at 59%, although 49% of the positive scans for primary tumor were unconfirmed and surgical histopathology was available in 17% of patients.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, additional evidence of metastatic lesions was evident in O30%, particularly when localized within the skeletal system (Buchmann et al 2007), and localization of unknown primary NENs was established in 39% of cases (Prasad et al 2010). The superiority of 68 Ga-DOTA-based PET/CT over anatomic imaging using CT or MRI and its impact on treatment were demonstrated in a recent study on 52 NEN patients who underwent both standard morphological imaging and 68 Ga-DOTATOC PET/CT (Frilling et al 2010).…”
Section: R166mentioning
confidence: 99%
“…68 Ga-DOTANOC is a somatostatin analog radiotracer that, compared with other 68 Ga-DOTA peptides, shows improved affinity to somatostatin receptor (SSTR) type 2 and high affinity to types 3 and 5 (6)(7)(8). 68 Ga-DOTANOC PET/CT has been used for staging, restaging, controlling therapy, and detecting unknown primary tumors in patients with NET (9)(10)(11). Compared with other radiopharmaceuticals, such as 18 F-FDG and 18 F-3,4-dihydroxyphenylalanine (12)(13)(14), or other conventional imaging methods, such as CT or bone scanning (15,16), 68 Ga-DOTANOC has proved to be more accurate in the diagnosis of NET.…”
mentioning
confidence: 99%